2000
DOI: 10.1007/pl00000211
|View full text |Cite
|
Sign up to set email alerts
|

The novel acute phase protein, IHRP, inhibits actin polymerization and phagocytosis of polymorphonuclear cells

Abstract: 1) IHRP may bind to actin released from the damaged cells and suppress its toxic action by preventing the formation of actin fibril. 2) IHRP may bind to cell surface actin on PMN cells and inhibit their phagocytic activities. 3) From these results, IHRP may act as an anti-inflammatory protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…The consistently low levels of haptoglobin (and precursor) as well as of hyaluronidase and IHRP in Hampshire pigs confirm the absence of inflammatory processes. Hence, hyaluronidase limits the permeability of the respiratory barrier, and IHRP is considered to reduce the phagocytic activity of PMN by inhibiting the polymerization of cell surface actin [8].…”
Section: Discussionmentioning
confidence: 99%
“…The consistently low levels of haptoglobin (and precursor) as well as of hyaluronidase and IHRP in Hampshire pigs confirm the absence of inflammatory processes. Hence, hyaluronidase limits the permeability of the respiratory barrier, and IHRP is considered to reduce the phagocytic activity of PMN by inhibiting the polymerization of cell surface actin [8].…”
Section: Discussionmentioning
confidence: 99%
“…Pig-MAP/ITH4 has been shown to be expressed in the endometrium during the oestrous cycle and early pregnancy in pigs [14]. Recent studies suggest that the ITIH4 may act as an anti-inflammatory protein since it has been shown that this protein can inhibit actin polymerisation and phagocytosis of polymorphonuclear cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…It does not have the conserved cleavage site of HC1-3 that allows them to link with bikunin. It does, however, bind to and block the polymerization of actin, resulting in inhibition of neutrophil phagocytosis and chemotaxis (21). The more recently described HC5 has not yet been fully characterized; nor has it been shown to complex with chondroitin sulfate to form I␣I (or pre-I␣I).…”
mentioning
confidence: 99%